An editorial view on the special issue "Colorectal cancers: from present problems to future solutions" - Allgayer, Heike (Cancers, 2022)
Colorectal cancer (CRC) represents one of the most frequent human cancer entities and is still amongst the “top killers” in human cancer, although fundamental progress has been made in recent years in CRC prevention, early diagnosis, basic and translational research, and (targeted) therapy [...]